A preliminary phylogeographic study of the diplurid genus microhexura - Martens, Mia M. (2005)
Microhexura spiders are the northernmost members of the family Diplurid, and are the smallest mygalomorph spiders, ranging from 2.5 to 5.6 mm in adult body length.There are two species, Microhexura idahoana and Microhexura montivaga (the Spruce-fir Moss Spider). Microhexura montivaga was placed on the endangered species list in1995. It has been found in only seven spruce-fir forest dominated sites and occurs at or above 1646 meters. Part of the U.S. Fish and Wildlife's recovery plan for the Spruce-fir Moss Spider is to genetically compare these populations.In this study, 13 M. montivaga specimens, including five from Mt. Buckley(Sevier Co., TN), five from Mt. LeConte (Sevier Co., TN), and three from Roan Mountain (Mitchell Co., NC). Six M idahoana specimens from Wasco Co., Oregon(used as a comparison for M montivaga) were also used for genetic analysis. One leg was removed from each field-caught spider. The spider was then observed to ensure that it was not killed during the procedure, and then released. Legs were transported to Western Carolina University where they were stored in a -80°C freezer. Subsequent DNA extractions, PCR, and sequencing of the CO1 gene were then done on the legs.Once sequences were obtained and aligned, base frequencies, a genetic similarity matrix showing pairwise distances within and between populations, neighbor-joining trees,cladograms (showing branch lengths), and an estimate of divergence was made using the molecular clock rate of 2.3% divergence per million years.Pairwise distances of M montivaga populations showed an increase in genetic diversity between populations as geographic distance increased, with specimens from Roan Mountain (the population farthest away geographically from the other two locations) showing a greater genetic distance when compared to the pairwise distance between Mt. Buckley and Mt. LeConte. The neighbor-joining trees also showed Roan Mountain specimens to be separated in their own clade. The molecular clock data suggested that Roan Mountain specimens had been isolated from Mt. Buckley and Mt.LeConte specimens since the Pliocene era (3.48 million years ago), whereas Mt. Buckley had been isolated from Mt. LeConte during the Pleistocene (17,826 years ago). Microhexura idahoana diverged from M montivaga during the Miocene (8.37 million years ago). These data suggest managing the Spruce-fir Moss Spider as isolated populations with little gene flow. In order to save the Spruce-fir Moss Spider, a more extensive phylogeographic study and a plan of action on how to prevent future habitat loss and restore current habitat are needed.